A review on digital multimodal composing in post-secondary EFL context: Practices and implications - Lanoke Intan Paradita (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
The availability of texts and how they are produced have become more multimodal, along with the rapid development of technology. In the English as Foreign Language (EFL) context, this change has influenced classroom instructions where digital multimodal composing (DMC) is incorporated into students’ meaning-making. This qualitative study aims to review recent studies on DMC in the post-secondary EFL contexts to find out the DMC tasks implemented in this setting and what implications have resulted from the tasks. Based on the analytical review of twenty empirical studies from 2015-2022, DMC was generally used to leverage students’ English language skills, train students’ digital literacy skills, advocate students’ voices, build learning engagement and investment, and increase students’ participation in collaborative projects. The implication of the studies showed that teacher support is needed and that the DMC tasks afford to expand students’ meaning-making. Future direction on DMC studies in the post-secondary EFL context is also discussed.